7 - Land use correlates of street children in Ogbomoso, Nigeria - Olufemi A. Fawole,; David V. Ogunkan,; Deborah S. Adekeye, (African Sociological Review, 2015)
Following the observation of increasing incidence of street children phenomenon in Nigerian urban centers, this study examines the relationship between land use and street children in Ogbomoso. Data on incidence of street children were obtained through the method of direct counting which was done on four different days of the week within defined Data Delineated Areas (DDAs) purposively selected across the residential zones of the city. The study employs z scores to compare the intensity of the problem across the selected DDAs. Data were also analyzed using pie chart, bar chart, graph and percentages. The study reveals that the incidence and categories of street children varies with land uses. It recommends, therefore that urban planners, governments as well as individuals have roles to play in proffering solutions to the menace. It also calls for more research works on the problem of street children.